Relationships between management practices and ground‐active invertebrate biodiversity in New Zealand kiwifruit orchards. (13th May 2015) - Todd, Jacqui H.; Malone, Louise A.; Benge, Jayson; Poulton, Joanne; Barraclough, Emma I.; Wohlers, Mark W.
Abstract: Increasing the biodiversity of agro‐ecosystems may benefit rare and native species, improve ecosystem services and increase grower incomes through higher value eco‐verified orchard products. Previous research has shown that the taxonomic richness of invertebrates in organic kiwifruit orchards is significantly higher than in integrated pest management (IPM) orchards, suggesting that orchard management practices may affect invertebrate biodiversity. We used multiple regression models to investigate the relationships between the diversity of ground‐active invertebrates in three functional groups [natural enemies, herbivores, detritivores (including fungivores)] and 14 management practices used on 10 organic and 10 IPM orchards. The significant relationships between the management variables and invertebrate communities differed for each functional group: (i) the greater diversity of natural enemy and detritivore taxa in organic orchards was significantly correlated with less toxic agrichemical sprays; (ii) greater amounts of vegetative ground cover in the organic orchards was significantly correlated with a greater diversity of detritivore and herbivore taxa; and (iii) differences in magnesium application rates explained some of the variation in the herbivore and detritivore communities. Management practices on IPM kiwifruit orchards could be altered to increase invertebrate biodiversity, which also may improve ecosystem services on these orchards; however, care should be taken to ensure that pest populations do not also benefit from these changes.